THE ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) PERSPECTIVE CALCULATION OF ENVIRONMENTAL MANAGEMENT ENVIRONMENT IN RIAU - Huseno, Tun (Jurnal Aplikasi Manajemen, 2018)
This study aimed to see the results of Environmental Management Accounting (EMA) analysis in application to the environmental costs of oil mining companies in Riau and their influence on the company. This analysis starts with the quantitative and descriptive analysis of primary data in the form of data on the profits of the company's petroleum production. Data form of the amount of the company's petroleum production per day and the amount of sales profit per day. The analysis by including aspects of costs that must be met by the company in Environmental Management Accounting (EMA). The results of the analysis show that there was a decline in company profits by 15% between entering environmental costs by not including environmental costs. However, the company still benefits from the economic side. In addition, the company's responsibility for the environment and society could be fulfilled.